Black Media Reporting on Theater, Dance, and Jazz Clubs in Canada: From Shuffle along to Rockhead’s Paradise - Thompson, Cheryl; Jabouin, Emilie (Journal of Communication Inquiry, 2021)
Canada has a history of de facto Jim Crow (1911–1954). It also has a historical Black press that is intimately connected to Black America through transnational conversations, and diasporic migration. This article argues that Canada’s Black newspapers played a pivotal role in promoting Black performance during a time when they were scarcely covered in the dominant media. Drawing on news coverage from the 1920s through 1950s of black dance, musicals, and jazz clubs this article examines three case studies: Shuffle Along (1921–1924), the first all- Black Broadway musical to appear at Toronto’s Royal Alexandra Theater, Alberta-born dancer Len Gibson (1926–2008), who revolutionized modern dance in Canada in the 1940s and 1950s, and the Montreal jazz club Rockhead’s Paradise (1928–1980), a pivotal site in the city’s Little Burgundy, a Black neighborhood that thrived in the 1930s through 1950s. The authors argue that when Black people were excluded from and/or derogatorily portrayed in the dominant media, Canada’s Black press celebrated collective achievement by authenticating Black performance. By incorporating Canada’s Black Press into conversations about Jim Crow and performance, we gain a deeper understanding of Black creative output and resistance during the period.